Menu scheduling for high blood pressure patient with optimization method through integer programming - Liew, Su Hui; Sufahani, Suliadi (International Journal of Multidisciplinary Research and Development, 2018)
The application of mathematical modelling technique was normally applied in various fields of study. It is the optimal solution that can help to solve various diet problems. Every diet problem has its specific objective functions and limitation of cost. The requirement of nutrient content, the amount of food intake and the price of food should be considered when planning a balanced diet menu. This paper focuses on the mathematical modelling techniques that are used by researchers in optimizing the diet problem and planning a diet menu that meet all the specification and constraints. Additionally, this paper demonstrates the usage of integer programming and improvement that can be done. An optimal approach is obtained to solve the menu scheduling for high blood pressure patient.